2014
DOI: 10.9738/intsurg-d-13-00016.1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Gastrectomy in Elderly Patients

Abstract: The decision to undergo surgery for gastric cancer patients aged !85 years should be made carefully. We retrospectively reviewed the prognostic factors of gastrectomy for 64 patients aged !85 years who had undergone curative gastrectomy for gastric cancer. The effects of various clinical characteristics and surgical interventions on survival were retrospectively analyzed. Univariate analysis revealed that sex (male/female; P ¼ 0.001), the extent of gastric resection (total/distal; P ¼ 0.028), the extent of lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However, procedure-associated morbidity remains high and this is a relevant issue for patients and treatment teams [19,20]. The fact that much older and severely co-morbid patients, as well as patients in advanced tumor stages and with compromised performance status are resected might partly explain this fact [3][4][5]. Nevertheless, high morbidity and mortality might also be associated with insufficient standardization of perioperative treatment, and in particular with so called "failure to rescue", a situation in which emerging complications are not detected and managed appropriately, resulting in the death of the patient [2,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, procedure-associated morbidity remains high and this is a relevant issue for patients and treatment teams [19,20]. The fact that much older and severely co-morbid patients, as well as patients in advanced tumor stages and with compromised performance status are resected might partly explain this fact [3][4][5]. Nevertheless, high morbidity and mortality might also be associated with insufficient standardization of perioperative treatment, and in particular with so called "failure to rescue", a situation in which emerging complications are not detected and managed appropriately, resulting in the death of the patient [2,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of improvements in surgical technique and perioperative management, surgery for gastric cancer remains challenging and patients who undergo radical resection are reported to have high complication rates [2,3]. One reason is that more and more elderly and multimorbid patients are resected [4,5]. On the other hand, due to preoperative malnutrition of patients with gastric neoplasms and chronic comorbidities, perioperative mortality can reach up to 8.8% [6].…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] It has been reported that assessments with these scoring systems do not re ect the prognosis of elderly patients. [16] There are some limitations in this study. First, this study is small-scale with a single institution.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have identi ed gender [16,17], surgical procedure [4,7], PNI [7,18] and postoperative complications [7,17], as predictors of OS for elderGC after gastrectomy. In our study, NLR and NRCmortality were found to be independent predictors of OS in addition to surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have identi ed sex, [18,19] PS, [19] surgical procedure, [4,7] PNI, [7,20] and postoperative complications, [7,19] as predictors of OS among elderly patients with gastric cancer after gastrectomy. In our study, NRC-mortality, in addition to PS and surgical procedure, was found to be the independent predictors of OS.…”
Section: Discussionmentioning
confidence: 99%